A Five-Factor Analysis Of Spirituality In Young Adults: Preliminary Evidence - Cramer, Robert J. (Research in the social scientific study of religion, 2008)
This study examines predictive relations of the Five-Factor Model (FFM) domains of personality in relation to two aspects of spirituality. Specifically, FFM domains were analyzed as predictors of Spiritual Life Integration (SLI) and Social Justice Commitment (SJC). Participants were 135 young adults (M = 18.82 years, SD = 1.07). Results showed that agreeableness and conscientiousness predicted SLI. Additionally, extraversion, agreeableness, and gender predicted SJC. Implications, limitations, and future directions are discussed in the framework of personality theory and construct validity for the Spiritual Involvement Scale (SIS).